English Language and Its Importance as Global Communication - I Wy Ana Kurniawan (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2024)
This study aimed at finding out the importance of English language as global communication. English has emerged as a dominant force in international discourse, playing a pivotal role in facilitating communication among people from diverse linguistic and cultural backgrounds in the global area or around the world. The study used literature study to gather the data from many sources especially in online form in research journal. This study found out that the importance of English language as global communication, basically has 4 major entities . Firstly, in education, English acts as the principal medium of instruction across various educational domains. In science and technology, it acts as a primary medium for communication, collaboration, and the dissemination of knowledge in these fields. In business, it acts as a global lingua franca, English effectively caters to the requirements of multinational corporations, serving as a communication conduit between various business entities. In travel and tourism, it acts as a crucial tool for communication, customer service, marketing, and information dissemination